2018
DOI: 10.1080/10640266.2018.1499337
|View full text |Cite
|
Sign up to set email alerts
|

Why do men stigmatize individuals with eating disorders more than women? Experimental evidence that sex differences in conformity to gender norms, not biological sex, drive eating disorders’ stigmatization

Abstract: Previous research has shown that men are more stigmatizing than women toward individuals with eating disorders, including anorexia nervosa and muscle dysmorphia. We hypothesized that previously observed sex differences in eating disorders' stigmatization are driven by sex differences in individuals' levels of conformity to masculine and feminine gender norms. Young adults (N = 545) completed validated measures of conformity to masculine and feminine norms and were then randomly assigned to read a character des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…Some studies found no gender difference in ED stigma [ 25 , 31 ], but Makowski et al [ 67 ] found that women reported more social distance from people with EDs. A recent study found that AN stigma was not predicted by gender per se , but rather by compliance with masculine gender norms, which resulted in more stigmatizing behavior toward people with AN [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found no gender difference in ED stigma [ 25 , 31 ], but Makowski et al [ 67 ] found that women reported more social distance from people with EDs. A recent study found that AN stigma was not predicted by gender per se , but rather by compliance with masculine gender norms, which resulted in more stigmatizing behavior toward people with AN [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 , 5 , 6 ]. More precisely, those works have also investigated the content and the distribution of ED stigma [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to men’s awareness that men are more likely than are women to stigmatize those with EDs (Griffiths et al, 2014). Notably, a recent study revealed that this effect may be driven by level of conformity to masculine norms (Austen & Griffiths, 2019). That is to say, the more pressure men place on themselves to adhere to the rigid and inflexible prescriptive stereotypes of manhood, the more stigma they attribute to individuals with EDs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a difference in the way men and women present as men may be striving to attain muscle mass [7], which may be viewed as normal and acceptable, hindering recognition of an ED. Modern Western culture floods men with messages about their appearance and body [9]; and there is extensive research highlighting how men feel the need to conform to the mesomorphic ideal [10][11][12][13]. It is believed that in Western societies men strive for defined muscle and low body fat, often following strict rules in order to achieve this [14] and as such their behaviours may be vastly different to those of a woman with an ED [15].…”
Section: Eating Disorders In Menmentioning
confidence: 99%